Analysis of raw chicken meat for microbiological quality - Baruah, Kashyap Kumar; Husain, Saiyyad Alamdar; Khan, Md. Meraj Ali (Journal of Postharvest Technology, 2024)
A study was conducted with a forty numbers of isolates from twenty fresh chicken meat samples of which 16 (40.00 percent) and 24 (60.00 percent) isolates were used in study. A total of 13 (32.50 percent) strains of coagulase negative Staphylococci, 5 (12.50 per cent) strains of Aeromonas spp. and 22 (55.00 per cent) strains of Salmonella spp. were isolated. The microbiological quality of chicken meat as observed by TVC was in the range of 4.70 to 8.60 log10 cfu/g with average TVC of 6.36 ± 1.19 to 6.92 ± 0.35 log10 cfu/g. The analysis of microbes in chickens muscle, liver, heart, and gizzard samples revealed the TVC (log10 cfu±SE) in the range of 6.02 to 7.80 (average 6.91± 2.13), 5.40 to 7.50 (average 6.45±1.27), 4.70 to 7.80 (average 6.36±1.19) and 4.95 to 8.60 (average 6.92 ±0.35), respectively. The investigation revealed that prevalence of Aeromonas spp. and coagulase negative Staphylococcus in muscle, liver, heart, gizzard were found to be 20 percent, 20 per cent 18 per cent and 60 per cent and that of coagulase negative Staphylococcus was 23.06 percent, 23.06 per cent 53.88 per cent and 0 per cent. The investigation also revealed the prevalence of Salmonella spp. present in muscle (31.88%), liver (31.86%), heart (0.0%) and gizzard (36.24%). The results recorded that 88.88% isolates of Salmonela spp. showed resistance towards Amoxycillin (30mcg) and Ampicillin (10mcg) and 71.42% isolates of Aeromonas spp. showed resistance towards Amoxycillin (30mcg) and Ampicilin (10mcg). Streptomycin (10mcg) showed 100% resistance to Staphylococcus isolates.